Osmostress response of the yeast Saccharomyces - Mager, Peter (2014)
Exposure of yeast cells to high osmolarities leads to dehydration, collapse of ion gradients over the plasma membrane and decrease in cell viability. The response of yeast cells to high external osmolarities is designated osmostress response. It is likely that both osmoregulatory and general stress reactions are involved in this so far poorly understood process. Part of the response aims at raising the internal osmotic potential, i.e. the production of osmolytes such as glycerol, and exclusion of toxic solutes. In addition, heat-shock proteins and trehalose are synthesized, probably to protect cellular components and to facilitate repair and recovery. Recent analyses of osmosensitive yeast mutants strongly suggest the involvement of protein kinase-mediated signal-transduction pathways in the maintenance of the osmotic integrity of the cell. This has stimulated interesting hypotheses as to the actual osmosensing mechanism.